Association of Sleep, Neuropsychological Performance, and Gray Matter Volume With Glymphatic Function in Community-Dwelling Older Adults. (22nd February 2022) - Siow, Tiing Yee; Toh, Cheng Hong; Hsu, Jung-Lung; Liu, Geng-Hao; Lee, Shwu-Hua; Chen, Ning-Hung; Fu, Changjui James; Castillo, Mauricio; Fang, Ji-Tseng
Abstract : Background and Objectives: The glymphatic system, which is robustly enabled during some stages of sleep, is a fluid-transport pathway that clears cerebral waste products. Most contemporary knowledge regarding the glymphatic system is inferred from rodent experiments and human research is limited. Our objective is to explore the associations between human glymphatic function, sleep, neuropsychological performance, and cerebral gray matter volumes. Methods: This cross-sectional study included individuals 60 years or older who had participated in the Integrating Systemic Data of Geriatric Medicine to Explore the Solution for Health Aging study between September 2019 and October 2020. Community-dwelling older adults were enrolled at 2 different sites. Participants with dementia, major depressive disorders, and other major organ system abnormalities were excluded. Sleep profile was accessed using questionnaires and polysomnography. Administered neuropsychological test batteries included Everyday Cognition (ECog) and the Consortium to Establish a Registry for Alzheimer's Disease Neuropsychological Battery (CERAD-NB). Gray matter volumes were estimated based on MRI. Diffusion tensor imaging analysis along the perivascular space (DTI-ALPS) index was used as the MRI marker of glymphatic function. Results: A total of 84 participants (mean [SD] age 73.3 [7.1] years, 47 [56.0%] women) were analyzed. Multivariate linear regression model determined that age (unstandardized β, −0.0025 [SE 0.0001]; p = 0.02), N2 sleep duration (unstandardized β, 0.0002 [SE 0.0001]; p = 0.04), and the apnea-hypopnea index (unstandardized β, −0.0011 [SE 0.0005]; p = 0.03) were independently associated with DTI-ALPS. Higher DTI-ALPS was associated with better ECog language scores (unstandardized β, −0.59 [SE 0.28]; p = 0.04) and better CERAD-NB word list learning delayed recall subtest scores (unstandardized β, 6.17 [SE 2.31]; p = 0.009) after covarying for age and education. Higher DTI-ALPS was also associated with higher gray matter volume (unstandardized β, 107.00 [SE 43.65]; p = 0.02) after controlling for age, sex, and total intracranial volume. Discussion: Significant associations were identified between glymphatic function and sleep, stressing the importance of sleep for brain health. This study also revealed associations between DTI-ALPS, neuropsychological performance, and cerebral gray matter volumes, suggesting the potential of DTI-ALPS as a biomarker for cognitive disorders.